2007
DOI: 10.1124/jpet.106.109678
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the MCHR1 Antagonist N-[3-(1-{[4-(3,4-Difluorophenoxy)phenyl]methyl}(4-piperidyl))-4-methylphenyl]-2-methylpropanamide (SNAP 94847) in Mouse Models of Anxiety and Depression following Acute and Chronic Administration Is Independent of Hippocampal Neurogenesis

Abstract: Melanin-concentrating hormone (MCH) is a hypothalamic neuropeptide that plays a role in the modulation of food intake and mood. In rodents, the actions of MCH are mediated via the MCHR1 receptor. The goal of this study was to investigate the effects of acute (1 h) and chronic (28 days) p.o. dosing of a novel MCHR1 antagonist,phenyl]methyl}(4-piperidyl))-4-methylphenyl]-2-methylpropanamide (SNAP 94847), in three mouse models predictive of antidepressant/anxiolytic-like activity: novelty suppressed feeding (NSF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 39 publications
(61 reference statements)
6
88
1
Order By: Relevance
“…A causal relationship between the regulation of neurogenesis and behavioral responses has been suggested by studies demonstrating that the effects of chronic antidepressant administration require increased neurogenesis (13,14), although the current findings are correlative. However, two recent studies found neurogenesis-independent effects of antidepressants (15,16), indicating that alternate mechanisms underlie the behavioral responses (5). Previous studies have demonstrated that IL-1␤ produces a rapid and presumably neurogenesisindependent effect on behavioral despair (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A causal relationship between the regulation of neurogenesis and behavioral responses has been suggested by studies demonstrating that the effects of chronic antidepressant administration require increased neurogenesis (13,14), although the current findings are correlative. However, two recent studies found neurogenesis-independent effects of antidepressants (15,16), indicating that alternate mechanisms underlie the behavioral responses (5). Previous studies have demonstrated that IL-1␤ produces a rapid and presumably neurogenesisindependent effect on behavioral despair (36).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, antidepressant treatment increases hippocampal neurogenesis, blocks the antineurogenic effects of stress (11,12), and reduces or even reverses hippocampal atrophy (9, 11). Recent studies demonstrate that new hippocampal neurons are required for the actions of antidepressants in behavioral models of depression and anxiety (13, 14) with some exceptions (15,16).…”
mentioning
confidence: 99%
“…The inhibitory effect of TPI 1361-17 on cocaine self-administration, a dopamine-induced response, may seem contrary to the increased performance that another MCH1R antagonist, peptide 30 has in the forced swim test (19), a model where reduced dopamine levels correlate with increased depression-like state. However, it should be noted that the physiology of depression, more than that of cocaine addiction, involves the activities of neurotransmitter systems others than dopamine (48), and that, for unknown reasons, different MCH1R antagonists exert variable performance in antidepressant-like assays (49).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral response to forced swimming was measured as described in David et al (2007). Mice were placed in clear glass buckets 20 cm deep, filled 2/3 of the way with 25 1C water, and videotaped from the side.…”
Section: Nsfmentioning
confidence: 99%